Phytodiversity of Eringole Sacred Grove of Kerala - Das, Divya K.; Menon, A. R. R. (Indian Forester, 2011)
habitations of Perumbavoor Municipal area in Ernakulam District of Kerala State. The vegetation of the sacred groves is considered to be the remnants of the old cover types existed years before. Most of the groves are under heavy pressure of degradation, mainly due to anthropogenic influence. The present work envisages analyzing qualitatively and quantitatively, the plant diversity of the ecosystem.